2021
DOI: 10.1080/02640414.2021.1948259
|View full text |Cite
|
Sign up to set email alerts
|

The influence of growth and training loads on injury risk in competitive trampoline gymnasts

Abstract: There is currently limited research exploring the relationship between growth, training load and injury in gymnasts. Twenty-one national level, trampoline gymnasts recorded training load and injury for 8-weeks. Percentage of predicted adult height (%PAH) was calculated using the Khamis-Roche method and used to define growth spurt status. Training load was calculated using the session rate of perceived exertion and analysed as differential loads and as a 7-day exponentially weighted moving average (EWMA7day). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…There was inconsistent or limited evidence of a relationship between external training loads and injury. Twenty-two studies found significant relationships [ 35 , 37 39 , 52 , 57 , 59 , 60 , 62 , 65 , 66 , 68 , 77 82 , 87 89 , 94 ], whilst three had non-significant findings [ 43 , 58 , 85 ]. Of the studies that found significant results, one found that greater training load decreased the risk of injury in at least one variable [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was inconsistent or limited evidence of a relationship between external training loads and injury. Twenty-two studies found significant relationships [ 35 , 37 39 , 52 , 57 , 59 , 60 , 62 , 65 , 66 , 68 , 77 82 , 87 89 , 94 ], whilst three had non-significant findings [ 43 , 58 , 85 ]. Of the studies that found significant results, one found that greater training load decreased the risk of injury in at least one variable [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Growth-related apophysis/physis pathologies were not mentioned in most epidemiological studies concerning a population of university gymnasts, whereas in our study, it was the most frequent injury type. This has already been reported in competitive trampoline gymnasts, with growth-related apophysis/physis pathologies associated with the adolescent growth spurt and with higher weekly training loads 16. This is of great importance given the potential consequences in the short, middle and long terms of these specific injuries on the musculoskeletal systems (physical aspect) and psychological and societal aspects.…”
Section: Discussionmentioning
confidence: 67%
“…This deserves future studies to continue to improve WAG health protection. As practical approaches, following suggestions from trampoline gymnasts, education of coaches to identify periods of rapid growth and monitor training load could help 16 17. Our population and the university categories’ training and competition habits differed.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, becoming a health problem commonly accompanying children’s physical activity. In artistic gymnastics, it is most common due to a combination of two factors: young age (people who are not biologically mature) and the need to overcome a relatively heavy load during exercise, which is body weight [ 51 ]. A similar situation occurs in rock climbing, which is a young discipline commonly practiced by people of all ages [ 50 , 52 ].…”
Section: Discussionmentioning
confidence: 99%